Acceleration of Anti‐Markovnikov Hydroamination in the Synthesis of an Active Pharmaceutical Ingredient. Issue 10 (6th July 2016) - Mitic, Aleksandar; Skovby, Tommy; Dam‐Johansen, Kim; Gernaey, Krist V.
Abstract: Slow chemical reactions are a big challenge in the modern pharmaceutical industry. Their accelerations together with the introduction of continuous manufacturing modes are major drivers for future development. One example reaction is hydroamination, a reaction between unsaturated hydrocarbons and amines. Such a reaction type is the main focus of this work. More precisely, the anti‐Markovnikov hydroamination reaction between cis/trans 9 H ‐thioxanthene‐2‐chloro‐9‐(2‐propenylidene)‐(9CI) and 1‐(2‐hydroxyethyl)piperazine (HEP) is investigated in detail. It has been traditionally performed in toluene with a huge excess of HEP and reaction times of up to 24 h. Acceleration of the reaction from 24 down to 4 h is achieved by switching from batch operation mode in toluene to either solvent‐free batch mode or microwave‐assisted hydroamination with tetrahydrofuran as a solvent. Abstract : Slow chemical reactions are not suitable and a big challenge for continuous manufacturing modes in the modern pharmaceutical industry. It is therefore important to perform accelerations of such reactions. Significant speeding up of an anti‐Markovnikov hydroamination reaction is achieved either via microwave radiation with tetrahydrofuran as solvent or a solvent‐free approach.